THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. SARANG MAS SEJAHTERA - Dahmal Daulay; Tibrani Tibrani; Denny Ammari Ramadhan; Dede Suryatman (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the influence of work motivation, work discipline, and work environment on employee performance at PT Sarang Mas Sejahtera, an automotive distribution and sales company in Indonesia. Using a quantitative, causal‑associative design, data were collected from 75 employees through a Likert‑scale questionnaire and analyzed using multiple linear regression. The findings show that employees report good levels of work motivation, work discipline, work environment, and performance. The results indicate that work motivation, work discipline, and work environment each have a positive and statistically significant effect on employee performance. Simultaneously, the three variables explain 56% of the variance in performance, confirming the robustness of the proposed model. These findings support Social Exchange Theory and Expectancy Theory by demonstrating that fair rewards, clear rules, and a conducive work environment foster reciprocal employee responses in the form of higher performance. The study suggests that integrated management of motivation, discipline, and work environment is crucial for sustaining employee performance in competitive automotive distribution and sales settings, and recommends that future research incorporate additional factors such as leadership, competence, and reward systems to build a more comprehensive performance model.